TIM-1 As a Signal Receptor Triggers Dengue Virus-Induced Autophagy - Chu, Li-Wei; Yang, Chia-Jui; Peng, Kuan-Jen; Chen, Pei-Ling; Wang, Shuu-Jiun; Ping, Yueh-Hsin (International journal of molecular sciences, 2019)
Dengue virus (DENV) infection triggers the activation of autophagy to facilitate the viral replication cycle from various aspects. Although a number of stimulators are proposed to activate autophagy, none of them appears prior to the uncoating process. Given that T-cell immunoglobulin and mucin domain 1 (TIM-1) receptor is a putative DENV receptor and promotes apoptotic body clearance by autophagy induction, it raises the possibility that TIM-1 may participate in the activation of DENV-induced autophagy. In this study, confocal images first revealed the co-localization of TIM-1 with autophagosomes in DENV-induced autophagy rather than rapamycin-induced autophagy, suggesting the co-transportation of TIM-1 with DENV during infection. The treatment of siRNA to knockdown TIM-1 expression in DENV-infected GFP-microtubule-associated protein light chain 3 (LC3)-Huh7.5 cells revealed that TIM-1 is required not only for DENV cellular internalization but also for autophagy activation. Furthermore, knockdown p85, a subunit of phosphoinositide 3-kinases (PI3Ks), which is co-localized with TIM-1 at rab5-positive endosomes caused the reduction of autophagy, indicating that TIM-1-mediated DENV-induced autophagy requires p85. Taken together, the current study uncovered TIM-1 as a novel factor for triggering autophagy in DENV infection through TIM-1-p85 axis, in addition to serving as a DENV receptor.